P49 SENSITIZING GLIOBLASTOMA CELLS TO THERAPY BY TARGETING THE L-GLUTAMATE/L-CYSTINE ANTIPORTER SYSTEM XC- - Kolb, Anna (Oxford University Press, 2014)
INTRODUCTION: System xc-(SXC),a L-cystine/L-glutamate antiporter represents the primary non-vesicular route of glutamate release. Certain cancers,such as Glioblastoma multiforme(GBM),are unable to synthesise sufficient concentrations of L-cysteine,rendering them dependent on L-cystine influx via SXC. GBM is the most common type of brain tumour with a median survival of only 15 months, partly due to its high resistance to conventional therapy. SXC may contribute to the former,as L-cystine is essential for generation of Glutathione,which is involved in removal of xenobiotics. The FDA-approved SXC antagonist Sulfasalazine(SSZ) may be implemented to lower resistance to therapy in GBM. Therefore, I ascertained SXC expression in GBM and investigated the effect of SSZ on tumour viability and growth. METHOD: Expression of SXC and the effect of SSZ in combination with conventional treatment were analysed by immunostaining, Flow cytometry, Western Blot and qPCR of surgical specimen and patient-derived lines. Moreover,a pharmakokinetic study was carried out to assess bioavailability of SSZ and its metabolites in the brain. RESULTS: In vitro experiments show that targeting SXC with SSZ, while concomitantly treating with temozolomide, leads to a significant attenuation in growth and viability in vitro when compared to temozolomide treatment alone. CONCLUSION: The evidence collected,strongly hints towards an important role of SXC in conveying resistance to conventional therapy in GBM. Therefore, targeting the antiporter in vivo may confer a beneficial effect on survival. In future work the efficacy of combined treatment with SSZ and temozolomide will be evaluated in vivo,in order to indicate if there is any clinical utility.